The menstrual cycle and its effect on the immune status of female endurance runners - Burrows, M.; Bird, S. R.; Bishop, N. (Journal of Sports Sciences, 2002)
Twenty highly trained, eumenorrhoeic female endurance runners were studied over three consecutive menstrual cycles. Average training distance per week, total years training and mood states were recorded throughout the three cycles. Salivary progesterone and menstrual cycle diaries were recorded over the first two cycles to identify luteal phase onset and the presence of any menstrual irregularities. Saliva samples were collected daily over the third cycle for analysis of immunoglobulin A (IgA) concentration and secretion and saliva flow rate. Two-way analysis of variance (ANOVA) revealed no significant differences in mood states across the phases of the menstrual cycle (P > 0.05). Training logs indicated that training did not alter throughout the 3 month study. One-way ANOVA revealed no significant differences in IgA concentration (P = 0.92), secretion rate (P = 0.84) or saliva flow rate (P = 0.95) across the phases of the menstrual cycle. Pearson's product-moment correlation revealed no relationship between IgA concentration and progesterone between the phases of the cycle (r = 0.39). We conclude that, in ovulatory female endurance runners whose physical and emotional stress are stable, IgA concentration is not significantly affected by fluctuations in progesterone during the menstrual cycle.